Answer:
a) vcm = 5.06*10⁻³ m/s
b) vcm = 5.06*10⁻³ m/s
Step-by-step explanation:
v₁ = 3.40*10⁴ m/s
v₂ = 0 m/s
m₁ = 1.05*10¹⁴ Kg
m₂ = 7.05*10²⁰ Kg
vcm initial = ?
vcm final = ?
a) Before the collision
vcm = (m₁*v₁ + m₂*v₂) / (m₁ + m₂)
vcm = (1.05*10¹⁴ Kg*3.40*10⁴ m/s + 7.05*10²⁰ Kg*0 m/s) / (1.05*10¹⁴ Kg + 7.05*10²⁰ Kg)
vcm = 5.06*10⁻³ m/s
a) After the collision
m₁*v₁ + m₂*v₂ = (m₁ + m₂)*vcm
⇒ vcm = (m₁*v₁ + m₂*v₂) / (m₁ + m₂)
vcm = (1.05*10¹⁴ Kg*3.40*10⁴ m/s + 7.05*10²⁰ Kg*0 m/s) / (1.05*10¹⁴ Kg + 7.05*10²⁰ Kg)
vcm = 5.06*10⁻³ m/s
The speed of the system's center of mass is the same value.